THE NEW PARADIGMS OF MANAGEMENT AT THE UNIVERSITY: GLOBALIZATION AND COMPETITIVENESS - Ríos Delgado, Teresa Jesús (2015)
This research links two existing paradigms of modern management such as globalization and competitiveness. Constant changes and rapid advances in science and technology require that university to build a horizontal relationship with society strengthening teaching skills and research trying to adapt to political, economic and social environmental changes becoming strategic unit to society. The university facing this new scenario has to face a world increasingly ruled by uncertainty and must adapt rapidly to the changes tied to economic, political, social transformations that are becoming faster. It is an applied and explanatory research since we seek to know the causal factors that explain our research problem. The hypothetical deductive method was used and as research techniques used were depth interviews and observation and documentary ones. It has been determined that public policy –related to higher education- is not taking in consideration globalization and competitiveness; without a joint of the infrastructure and the programs for the development of knowledge management as engine of the development of the country.